Assessment of genotypes of pigeonpea (Cajanus cajan) for higher productivity in semi-arid Vertisols - Choulwar, S B; Dahiphale, V V; Oza, S R; Maruthi Sankar, G R; Mishra, P K (The Indian Journal of Agricultural Sciences, 2012)
Field experiments of pigeonpea with 23 genotypes indicated that leaf water potential, RWC, number of pods/ plant have a moderate to high phenotypic and genotypic coefficient of variation. High heritability with genetic advance for these traits indicated selection for improving yield. BDN 2009 and K2 retained maximum leaf water potential, RWC and attained maximum number of pods/plant and yield. Based on ranks assigned to genotypes for performance of traits, K2 was superior with lowest rank sum in a Vertisol.